Money Demand and Inflation in Madagascar - Ben Nassar, Koffie (Washington, D.C. : International Monetary Fund, 2005)
This paper uses a two-sector model to estimate the relationship between prices, money, and the exchange rate in Madagascar during the period 1982-2004. The estimated model, using quarterly data, finds a stable long-run relationship among monetary aggregates, domestic prices, real income, and foreign interest rates. In addition, the error-correction model shows that changes in the monetary aggregates, the exchange rate, and foreign interest rates exert a significant impact on inflation. The results also suggest that a disequilibrium in the money market has a lasting impact on inflation. The paper concludes with policy recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet